supervisi Pentingnya Supervisi Pendidikan Untuk Mengembangkan Karakter Siswa - Triani , Defi; Putri, Cantika Maharani; Rizqa, Miftahir (Progressive of Cognitive and Ability, 2024)
This research describes the importance of educational supervision in developing student character. In this research, the method used is a literature study taken from previous books or journal sources related to the topic under study. The research results show that the importance of educational supervision in developing student character depends on the role of a teacher at school and that adequate supervision can help teachers improve the quality of learning, instill positive values ​​in students, create a conducive learning environment, and increase student learning motivation.